(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
Tridacna (kima) is a giant bivalve that is important to ecology. Attractive sizes and colours are the main attraction of overexploitation. Protection must occur, such as density measurement, size variations, and species identification based on morphology and DNA barcodes. This study aimed to identify clams using the DNA barcode method and to evaluate their population size and density in North Maluku waters. The research method uses DNA barcodes, morphological identification of mantle colour and shell size variations, and measurements of the density of clams found in North Maluku waters. The results were helpful based on DNA barcoding. They helped detect the morphology of the same results. Namely, three types of clams, Tridacna crocea, Tridacna squamosa, and Tridacna maxima, were detected. Differences in the shell’s size and shape and the mantle’s colour strengthen the three types as distinct species. In addition, the clade shape of the phylogenetic tree between the samples and GenBank data from the same clade. The condition of clam density in these waters showed the same results as other locations, namely less than 1/m2. A value density of < 1 m2 may suggest that the species is declining or lead to over-exploitation. Thus, this research data can be used as a reference for assessing chemical conservation activities.